On the shape of luminosity profiles of dwarf galaxies as a distance indicator: the NGC 5044 Group revisited - Cellone, Sergio Aldo (2001)
Conflicting evidence has been recently raised in order to use surface brightness profiles of dwarf galaxies as a distance indicator. In this paper we discuss in some detail the main error sources in profile fitting procedures for galaxies with more than one physical component, showing their impact on the resulting shape parameters. The apparent tight coupling between shape parameter and (pseudo) scalelength in the Sérsic law is especially dealt with, demonstrating that this relationship is mostly a mathematical artifact, thus throwing doubts on its usefulness as a distance indicator. Galaxies departing from the luminosity-shape relation are shown to exhibit different kinds of intrinsic peculiarities, thus prompting for better securing the empirical constraints to conform observational samples. As a relevant example in this sense, new observations of the galaxy N50 in the NGC 5044 Group are presented. We show that this object may be at an intermediate evolutionary stage between blue compact dwarfs (BCDs) and dwarf ellipticals (dEs).